Conselho de Segurança e a Guerra Civil da Síria: uma análise do posicionamento da Rússia - Silva, Evellin Cristina da (2021)
What explains the non-cooperation in an institutional body created to promote political coordination? The present work consists of a case study of the position of Russia in the United Nations Security Council (UNSC) during the Syrian Civil War, investigating the possible motivations for the lack of consensus and cooperation in that body in relation to the Syrian conflict. The Syrian Civil War began after popular demonstrations in 2011 and continues to this day. As the armed conflict unfolded, several groups emerged seeking to seize power and remove Bashar al-Assad from the presidency. However, opposition to the regime is diverse and consists of armed non-state actors and regional and global powers. President Assad also received external support, mainly from Russia, in order to keep himself in power and regain territories dominated by the opposition. Because of these involvements and clashes between these groups, the war became more complex and the main consequences reached civilians, as they had to move or seek refuge in other countries. In addition, years of armed conflict have resulted in numerous deaths and an unprecedented humanitarian crisis, which is why action is expected to resolve the problem. In this scenario, the UNSC would be important for being an agency responsible for maintaining peace and security and for approving intervention in extreme cases, but in the case of Syria there was a lack of consensus and cooperation for the resolution of the conflict did not happen. This lack of consensus had as a central factor the veto of Russia, along with the vetoes of another permanent member of the UNSC, China. Based on the theoretical approach of the literature on international cooperation and using documentary research as a method of data collection, based on UNSC reports and resolutions. This study of the Russian case in the Syrian conflict explores the motivations for the political positioning of one of the most important actors in the international security system. As a result of this research, the main Russian motivations for the veto motivated by economic issues are highlighted, given the existence of a partnership with Syria; strategic and security issues, due to the geopolitical position in the Middle East; and the Russian goal of remaining a central actor internationally.